الالتزام الإسلامي في الأعمال النثرية لسعاد الناصر :‏ ‏دراسة تحليلية نقدية /‏ - Ashwaq Ismail Batu Bara (Kulliyah Ma'arif al-Wahy wa-al-'Ulum al-Insaniyah, al-Jami'ah al-Islamiyah al-'Alamiyah Maliziya, 2010)
This study examines the literary works of Suad al-Naser. It focuses on the writer's prose i.e. articles and short stories. The main objective of this study is to explore the concept of Islamic Commitment or “al-Iltizam al-Islami" in discussing social issues and the means used to express this concept in an aesthetical form of writing. The study reveals that the writer has extensively used this concept of Islamic Commitment or “al-Iltizam al-Islami" in her works. This implies that Suad al-Naser has the ability to bring out the Islamic world view in her works. Not only that, the writer has successfully produced various articles that assist in the shaping of the human reformation. Finally, the study also reveals the writer's ability to create a balance between the concept of Islamic Commitment or “al-Iltizam al-Islami" with the element of creativity in her articles and short stories.